Why content matters. Zuckerberg, Vox Media and the Cambridge Analytica data leak - Lapaire (Bordeaux Montaigne), Jean-Rémi (ANTARES: Letras e Humanidades, 2018)
Following a major data breach scandal, Facebook CEO Mark Zuckerberg found himself at the center of a heated privacy row. The personal Facebook profiles of over 87 million users were unethically “harvested” by a Cambridge professor, using a deceptive personality quiz app and a web “scraper.” The rich data set was then transferred to Cambridge Analytica, a British political consulting firm, which used it to build models of voting behavior and influence voters in Donald Trump’s 2016 Presidential Campaign. Zuckerberg was held accountable for the leak. He offered vague apologies for the “breach of trust” that had occurred but refused to take the blame for data misuse. This article examines his line of defense and subtle evasion tactics, from a cognitive linguistics and gesture studies perspective.